2014
DOI: 10.1016/j.snb.2013.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Experimental measurement of human oocyte mechanical properties on a micro and nanoforce sensing platform based on magnetic springs

Abstract: This article presents a new micro and nanoforce sensor used to perform a mechanical characterisation of human oocytes. This device is based on the use of low-stiffness magnetic springs. The oocytes to be characterised are placed on a force-sensitive platform. A manipulator equipped with a standard micropipette is used to mechanically compress the oocyte. Some complete "force-compression length" curves associated with mechanical load-unload cycles are given. These curves show the linear, the non-linear and also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The oocyte behaviour during the loading cycle is linear. The difference detected between the load and the unload is the hysteresis due to the viscoelastic nature of the oocyte in accordance with the results obtained by Abadie et al [17].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The oocyte behaviour during the loading cycle is linear. The difference detected between the load and the unload is the hysteresis due to the viscoelastic nature of the oocyte in accordance with the results obtained by Abadie et al [17].…”
Section: Resultssupporting
confidence: 92%
“…One can mention the robochip system [16] which consists in compressing the oocyte against a magnetic force sensor using a probe, or the micro and nanoforce sensing platform based on passive magnetic springs [17,18] which compresses the oocyte against the border of a well located at the center of a specifically designed Petri dish. These studies have demonstrated that the mechanical behavior of an oocyte evolves and depends on its maturity stage [12,13,19,17]. However, and at least in France, using these devices with human oocytes requires the approval of the "'Agence de Biomédecine"' (public organization under the supervision of the french Minister of Health) which may be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…There are also other possible applications of PyC for measuring weak contact forces [27,28]. Indeed, the present device could be used for this but only using a linear component of magnetic spring along either a single horizontal axis or vertical axis.…”
Section: Resultsmentioning
confidence: 99%
“…1 the experimental result show a non-linear behaviour with differing loading/unloading paths. Due to quasi-static velocity plastic deformations are assumed and already reported [7]. The optimised parameter sets for the 12 indentations are listed in Tab.…”
Section: Resultsmentioning
confidence: 99%